2011
DOI: 10.1002/anie.201007896
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Regioselectivity of the Tryptophan 7‐Halogenase PrnA by Site‐Directed Mutagenesis

Abstract: Creating more space in the active site of the tryptophan 7‐halogenase PrnA by exchanging the large amino acid phenylalanine for the smaller alanine makes it possible for the substrate to bind in different orientations (see picture; yellow PrnA, blue PrnAF103A variant). This results in halogenation of the differently bound substrate in the 5‐position of the indole ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 20 publications
1
74
0
1
Order By: Relevance
“…Notably, the active site of Bmp2-TM exhibited no perturbation of the bound FAD cofactor with respect to WT Bmp2, nor did it lead to any apparent change in halogen binding properties of the enzyme, as demonstrated by conservation of its specificity for bromide. Already, for flavin-dependent tryptophan halogenases, it has been demonstrated that amino acid side chains that constitute the substrate binding site control the regiochemical outcomes for halogen additions (17,24,25 this observation to flavin-dependent halogenases that catalyze halogenation of aromatic substrates acylated to ACPs in demonstrating that side chains of residues lining the putative halogenase active site play a role in controlling substrate access, and potentially in specifying the positions on the pyrrole ring that are accessible to halogenation. Unfortunately, in the case of Mpy16, efforts to alter the putative substrate-binding cavity to resemble that of Bmp2 resulted in insolubility of the mutant Mpy16 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the active site of Bmp2-TM exhibited no perturbation of the bound FAD cofactor with respect to WT Bmp2, nor did it lead to any apparent change in halogen binding properties of the enzyme, as demonstrated by conservation of its specificity for bromide. Already, for flavin-dependent tryptophan halogenases, it has been demonstrated that amino acid side chains that constitute the substrate binding site control the regiochemical outcomes for halogen additions (17,24,25 this observation to flavin-dependent halogenases that catalyze halogenation of aromatic substrates acylated to ACPs in demonstrating that side chains of residues lining the putative halogenase active site play a role in controlling substrate access, and potentially in specifying the positions on the pyrrole ring that are accessible to halogenation. Unfortunately, in the case of Mpy16, efforts to alter the putative substrate-binding cavity to resemble that of Bmp2 resulted in insolubility of the mutant Mpy16 enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…As the monooxygenase screening methods reported so far are dependent upon detection of a specific reaction product or sequence of reactions occurring, they are not appropriate for application to the flavin-dependent halogenases, although methods which could be applied to their directed evolution are slowly emerging and have been demonstrated feasible. 223,240,241 In combination with what is known about the modification of their substrate scope, regioselectivity and stability through mutagenesis, 150,155,[222][223][224][225] in addition to the discovery of naturally-occurring thermostable Fl-Hals, 145 a number of reliable starting points for further engineering efforts are known.…”
Section: 113mentioning
confidence: 99%
“…Protein engineering of an FDH by rational site-specific mutagenesis was first reported in 2011 in which mutant F103A of the halogenase PrnA was found to change the strict 7-selectivity of WT to a 2 : 1 mixture of the 7-and 5-chlorinated products. 53 In other early work, rational design on the basis of structure-guided mutagenesis was applied to other FDHs with notable changes in site-selectivity in reactions of structurally different substrates, although a 100% shift in selectivity remains to be achieved. 54,55 Directed evolution of halogenases offers a more general and reliable solution to the problem of controlling the regioselectivity of halogenation.…”
Section: Engineering Site-selectivity Of Halogenasesmentioning
confidence: 99%